P094 An assessment of risk factors for HSV-2 infection in Malawian women using two classifications for the herpeselect 2 test. (14th July 2019) - Chakraborty, Payal; Norris, Alison; Huber-Krum, Sarah; Garver, Sarah; Hood, Robert; Banda, Venson; Turner, Abigail Norris
Abstract : Background: The Focus HerpeSelect 2 ELISA IgG Test, used to diagnose herpes simplex virus type 2 (HSV-2) infection, is inexpensive, convenient, and widely used. However, past studies document poor specificity of this test in African populations. Increasing the index value cutpoint for a positive result improves specificity, but no studies to our knowledge have examined whether the correlates of HSV-2 infection change when the cutpoint for positivity changes. We investigated whether associations between select demographic and sexual risk factors and HSV-2 serostatus varied when the cutpoint for positivity was increased. Methods: We sampled women (n=218) from the Umoyo wa Thanzi project, an ongoing community-based cohort study in rural Malawi. Using multinomial logistic regression and accounting for village-level clustering, we examined unadjusted and adjusted associations between select risk factors and HSV-2 serostatus. HSV-2 serostatus was coded in two ways: the manufacturer's recommended cutpoints (<0.9=negative, 0.9–1.1=indeterminate, >1.1=positive), and modified cutpoints (<0.9=negative, 0.9–3.5=indeterminate, >3.5=positive). Results: We assessed associations between HSV-2 serostatus and age, bacterial vaginosis (BV), and partner concurrency under each set of cutpoints. Measures of effect were weaker using the manufacturer's cutpoints compared to the modified cutpoints. Age was not significantly correlated with positive vs. negative serostatus using the manufacturer's cutpoint (relative risk ratio (RRR)=1.03, 95% CI: 0.97–1.09), but the association strengthened using the modified cutpoint (RRR=1.09, 95% CI: 1.01–1.17). Using the manufacturer's cutpoint, the RRR for BV was 1.73 (95% CI: 0.71–4.19) vs. RRR=2.70 (95% CI: 0.94–7.79) for the modified cutpoint. For partner concurrency, the RRR using the manufacturer's cutpoint was 1.47 (95% CI: 0.71–3.07), vs. RRR=3.45 (95% CI: 1.12–10.57) for the modified threshold. Conclusion: Changing the test cutpoints affected observed associations with previously-identified HSV-2 risk factors. HSV-2 prevention interventions informed by correlates of HSV-2 infection must be aware that different target populations may emerge depending on which cutpoints are adopted. Disclosure: No significant relationships.